Resistance inducers in disease control in wheat crops: A literature review about the content (Research, Society and Development, 2025)
When talking about the quality of wheat grain, it is common to relate this aspect to different growing conditions, including soil characteristics, temperature, humidity, presence of diseases and crop management. All of these factors have a direct impact on the industrial use of the final product. Therefore, it is essential to prevent and control diseases that affect this crop, seeking substances that make management more efficient and economical. In this context, inducing resistance in wheat plants can help reduce the incidence of diseases and increase productivity. The objective of this research was to conduct a bibliographical review and analyze research available in the literature on the use of resistance inducers in the control of diseases in wheat crops. Studies demonstrate that the use of elicitors contributes to increasing plant height, producing better quality grains, and also improving plant vigor. All the studies mentioned argue that silicate fertilizer is an alternative that promotes good results. Furthermore, silicon fertilizer combined with biostimulants promotes even more significant results. It is recommended that future research further explore the performance of resistance inducers against pathogens in wheat crops, as evidence indicates positive results.